1990
DOI: 10.1079/bjn19900098
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of purine derivatives by ruminants: effect of exogenous nucleic acid supply on purine derivative excretion by sheep

Abstract: The present study examined the relationship between the supply of exogenous nucleic acid (NA) purines and their recovery as the derivatives hypoxanthine, xanthine, uric acid and allantoin in urine. Six lambs, totally nourished by intragastric infusions of volatile fatty acids (VFA) and casein (i.e. no rumen fermentation), were given by abomasal infusion a microbial NA concentrate at six levels (from zero to 24.5 mmol purines/d). The true digestibility between the abomasum and terminal ileum of the NA purines w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
185
1
2

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(204 citation statements)
references
References 16 publications
16
185
1
2
Order By: Relevance
“…Initially proposed to be applied in sheep (Pé rez et al, 1998), the method based on the urinary dilution of labelled exogenous purines allows determination of the endogenous component of the urinary PD without having any adverse physiological effect on the animals. Using that method in sheep, the above authors obtained an endogenous excretion of 115.2 mmol/kg LW 0.75 , which was in the range (92 to 150 mmol/kg LW 0.75 ) reported by non-isotopic studies based on intragastric or digesta draining methods (Ørskov et al, 1979;Giesecke et al, 1984;Chen et al, 1990;Balcells et al, 1991). Furthermore, the technique has been used in lactating cows , showing that recycling of exogenous PB into the tissues by the salvage mechanism was negligible .…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Initially proposed to be applied in sheep (Pé rez et al, 1998), the method based on the urinary dilution of labelled exogenous purines allows determination of the endogenous component of the urinary PD without having any adverse physiological effect on the animals. Using that method in sheep, the above authors obtained an endogenous excretion of 115.2 mmol/kg LW 0.75 , which was in the range (92 to 150 mmol/kg LW 0.75 ) reported by non-isotopic studies based on intragastric or digesta draining methods (Ørskov et al, 1979;Giesecke et al, 1984;Chen et al, 1990;Balcells et al, 1991). Furthermore, the technique has been used in lactating cows , showing that recycling of exogenous PB into the tissues by the salvage mechanism was negligible .…”
Section: Discussionmentioning
confidence: 63%
“…The urinary recovery of PD in lactating goats was in the range observed in cattle 0.75 to 0.8 (Orellana-Boero et al, 2001;Verbic et al, 1990) sheep, (0.7 to 0.8; Balcells et al, 1991;Chen et al, 1990) and camels (0.72; Guerouali et al, 2004), but was higher than the recovery in buffaloes (0.11, Pimpa et al, 2003).…”
Section: Duodenal Input and Urinary Outputmentioning
confidence: 71%
“…Disappearance of RNA due to digestion and absorption has been shown to be almost complete as digesta enters the jejunum (McAllan, 1980;Schonhusen et al, 1999). When corrected for endogenous losses, true digestibility coefficients of 0.859, 0.780-0.871 and 0.913, have been reported for microbial NA-N (Storm and0rskov, 1983), RNA-N Schonhusen et al, 1999) and purines (Chen et al, 1990a), respectively.…”
Section: Digestion Of Nucleic Acidsmentioning
confidence: 91%
“…In vitro studies of purine absorption in the hamster have shown that hypoxantine, xanthine and to a lesser extent uric acid are preferentially excreted rather than absorbed across the intestine (Berlin and Hawkins, 1968), while studies in sheep have indicated that the capacity of the small intestine to absorb allantoin is limited (Chen et al, 1990b). Nucleic acids, free bases (except xanthine) and PDs entering the large intestine do not appear to be absorbed due to extensive degradation by indigenous microbes (Sorensen, 1960;Ellis and Bleichner, 1969a;Chen et al, 1990a), and therefore purines excreted in faeces appear to be primarily derived from microbes residing in the caecum (Surra et al, 1997b). Furthermore, variations in the supply of NAs entering the caecum and the extent of hindgut fermentation do not appear to affect urinary PD excretion, but there is evidence to suggest that it is positively influenced by the flow of undigested fibre in the duodenum (Surra et al, 1997b).…”
Section: Digestion Of Nucleic Acidsmentioning
confidence: 99%
“…Purine derivative excretion is an indirect method that does not account for these differences. Some purine derivatives also may be of dietary origin, and excretion route may vary with the nutritional and physiological status of the animal (Chen et al, 1990;Gonzá lez-Ronquillo et al, 2004). Thus, relative differences between dietary treatments in microbial CP flow may not be detected using this method.…”
Section: Introductionmentioning
confidence: 99%